The Petronas Twin Towers and the Kuala Lumpur City Centre from the perspective of critical regionalism [electronic resource] - Ismaeel Otuoze Audu, 1985- (2012)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2012